Characteristics of immune cell infiltration in inflamed mucosa of ulcerative colitis patients, hub gene candidates and key pathways in intestinal macrophage expression - Yiqiu Peng; Zilu Cui; Yingying Li; Yuxi Yang; Ruixia Liu; Yingyi Luan; Chenghong Yin (All Life, 2023)
Background: The ulcerative colitis (UC) associated immune cell network was revealed by analyzing the immune cell composition of inflamed and uninflamed mucosal biopsy samples from the same patients with UC. For differentially expressed macrophages, the differentially expressed genes (DEGs), functional enrichment analyses, and protein–protein interaction (PPI) network was analyzed to understand further the role of macrophages in the occurrence and development of disease. Methods: GSE 179285 dataset and GSE123141 dataset were downloaded from the GEO database. We used the CIBERSORT algorithm to map immune cell infiltration between paired inflamed and uninflamed intestinal mucosal biopsies. GO and KEGG functional enrichment analyses were used to analyze DEGs in intestinal macrophage populations. The PPI network was constructed by the Search Tool for the Retrieval of Interacting Genes (STRING) database. Immunohistochemistry and qPCR were used to verify hub genes in the mouse model of UC. Results: The inflamed tissues had a higher infiltration of M1 macrophages and M0 macrophages. M2 macrophages, naive B cells, gamma delta T cells (γδT cells), and resting mast cells were more abundant in uninflamed tissues. Functional enrichment analyses showed that the 141 DEGs are involved in multiple processes in the inflammatory response. The three genes (LCN2, CXCL1, SAA1) had the highest degrees of connectivity and may be hub genes. LCN2 was significantly overexpressed in colitis tissues compared with normal control tissues in the mouse model of UC. Conclusion: Changes in macrophages were notable in the inflamed mucosa of UC patients. 141 DEGs were entered into GO and KEGG functional enrichment analyses; three hub gene candidates were selected. Highlights: There were significant differences in the distribution of macrophages in the inflamed and uninflamed mucosa of UC patients. Functional enrichment analyses of DEGs in UC-associated intestinal macrophages were displayed. Three genes (LCN2, CXCL1, SAA1) were identified as hub gene candidates.